1998
DOI: 10.1002/(sici)1096-8644(199803)105:3<377::aid-ajpa7>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Finger ridge-count asymmetry and diversity in Andean Indians and interpopulation comparisons

Abstract: A separate analysis of ulnar and radial finger ridge-counts, obtained from 115 Aymara Indians (55 males and 60 females) of northern Chile, was performed. From these variables, directional asymmetry, fluctuating asymmetry, indices of bilateral asymmetry (square root of A2), and intraindividual diversity (s/square root of 5) were calculated for each sex. The results show that most bimanual differences for the ridge-counts are not statistically significant in the Aymara, except for radial counts in female first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Hall and Kimura (1994) reported that women and homosexual men were more likely to have a leftward laterality in finger ridges when compared to heterosexual men. Micle and Kobyliansky (1988) did not find a sex difference in ridge count DA, and Dittmar (1998) found a difference in only one of the five finger pairs. Furthermore, Mustanski et al (2002) were not able to replicate either the sex effect or the sexual orientation effect on laterality that Hall and Kimura had found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hall and Kimura (1994) reported that women and homosexual men were more likely to have a leftward laterality in finger ridges when compared to heterosexual men. Micle and Kobyliansky (1988) did not find a sex difference in ridge count DA, and Dittmar (1998) found a difference in only one of the five finger pairs. Furthermore, Mustanski et al (2002) were not able to replicate either the sex effect or the sexual orientation effect on laterality that Hall and Kimura had found.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the dermatoglyphic results of Hall and Kimura (1994), in our study heterosexual women and homosexual men had opposite DA in second digit length, i.e., heterosexual women had predominately rightward DA and homosexual men had leftward DA. Dittmar (1998) correlated asymmetry levels in ridge count from different digit pairs and found that the asymmetry in one digit usually did not predict the asymmetry in its neighbors. We found significant positive correlations between hand width and hand length DA in heterosexuals but not in homosexuals, and we found positive correlations between second and fourth digit DA in one of our datasets (Pittsburgh) but not the other (Berkeley).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even when the areas analysed for thumbprint ridge density in our study differ from that of the earlier studies, [2][3][4][5][6][12][13][14][15][16][17][18][22][23][24][25][26][27][28] the basic quantitative differences remain the same, i.e., females have a higher finger (thumb) print ridge density than males which is in accordance with earlier studies on different ethnic groups. 2,[5][6][7][8][13][14][15][16][17][18][22][23][24][25][26][27][28] Ridge thickness and furrows are the two important factors which determine the density of ridges. Cummins et al, 24 Ohler et al, 25 Kralik et al 26 and Moore 28 worked on the ridge thickness in fingerprints and showed that males have coarser finger ridges than females which suggests that males will have less ridges in a given area than females and thus a lower ridge density.…”
Section: Roc Locmentioning
confidence: 99%
“…1 Amongst the number of parameters available for establishing the identity of an individual, fingerprints are considered to be the most precise and reliable indicators of personal and gender identification. [2][3][4][5][6][7][8] No two fingers are found to have identical prints, and it is an overwhelming mathematical probability that no two will ever be found to match. 9 It has been estimated that chances of two persons having identical finger impressions are about one in sixty-four thousand million of the world population.…”
Section: Introductionmentioning
confidence: 99%
“…Among the number of parameters available for establishing the identity of an individual, fingerprints are extensively used in providing a clue regarding identity. [1][2][3][4][5][6][7] No two fingers are found to have identical prints, and it is an overwhelming mathematical probability that no two ever will be found to match. 8 The ridge patterns are formed in the human fetus before birth and remain the same throughout a person's life and even after death until they are lost through decomposition.…”
Section: Introductionmentioning
confidence: 99%